THE DIVINE AND SECULAR INTERPRETATION OF LOVE IN THE WORKS OF ALISHER NAVOI - Azimbayeva Soniya Marat kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the divine and secular interpretation of love in the works of Alisher Navoi, one of the greatest representatives of classical Eastern literature and the founder of the Uzbek literary language. Love occupies a central place in Navoi’s literary heritage and appears as a complex artistic, philosophical, moral, and spiritual concept. In his poems and epics, love is not limited to a simple emotional relationship between a lover and a beloved. It is presented as a force that reveals the inner world of a human being, educates the soul, strengthens moral qualities, and leads a person toward spiritual perfection. The article examines two main dimensions of love in Navoi’s works: secular love and divine love. Secular love is interpreted as a reflection of human emotions, beauty, loyalty, longing, suffering, and devotion. Through this form of love, Navoi describes the emotional experiences of human life and shows the moral values connected with sincerity, patience, and faithfulness. Divine love, on the other hand, is analyzed as a spiritual path that expresses the soul’s desire to reach truth, divine beauty, and closeness to God. In this sense, the image of the beloved often receives a symbolic meaning, while the suffering of the lover represents spiritual purification and moral growth. Special attention is given to the influence of Sufi ideas on Navoi’s interpretation of love. The article shows that the poet skillfully combines earthly feelings with spiritual meanings and presents love as a bridge between the human heart and divine truth. The symbolic images of the lover, the beloved, separation, beauty, suffering, and devotion serve to express both worldly emotions and mystical ideas. As a result, love in Navoi’s works becomes not only an aesthetic theme but also an important means of moral education and philosophical reflection. The relevance of this article lies in the fact that studying the divine and secular interpretation of love in Alisher Navoi’s works helps to understand the depth of his worldview, the humanistic essence of his poetry, and the spiritual richness of classical Uzbek literature. The article concludes that secular and divine love in Navoi’s literary heritage are closely interconnected and complete each other. Worldly love reveals the beauty and complexity of human feelings, while divine love gives these feelings higher spiritual meaning. Therefore, Navoi’s concept of love remains significant for understanding human nature, moral perfection, and the relationship between earthly life and spiritual truth.